Quality Performance of Teachers: Work Environment, Work Attitude, and Principal Supervision: Qualitative Investigation - Osias Kit T. Kilag; Ma. Felina S. Calledo; Francisca T. Uy; Yolanda T. Dela Cerna; Neil Andrian A. Angtud; Khen M. Villanueva (Future Science, 2023)
One of the most important factors in the face of the educational system is the quality of teachers' performance. The goal of this study is to ascertain whether the teachers' high-quality performance is actually impacted by the work environment, work attitude, and principal supervision. In this qualitative investigation, the Heideggerian Phenomenology design was employed. This study seeks to comprehend the phenomenon from the participant's point of view and through their experiences. In this study, the purposive method was employed, and participants were chosen to expound on their experiences as general education teachers at PAU Excellencia Global Academy Foundation, Inc., teaching in an inclusion classroom. It has been discovered that the key to creating a positive learning environment in the classroom is workgroup encouragement, especially having good relationships with the principal. How frequently teachers must deal with unruly and aggressive students have largely defined teaching obstacles. A teacher's perception of the supportive environment at school improved as he or she gained experience.